Multi Criteria Decision Analysis Berbasis Fuzzy Set Theory untuk Pengambilan Keputusan - Taufiq Rochman (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2006)
The aim of this study is to develop a framework for decision making process that incorporatesselecting the best alternative which is relevant to decision maker. Multi criteria decision anlysis based fuzzy set theory is used in this study to help decision maker to compare and rank decision alternative. This result anbles decision makers to collate the decision alternative and also permits decision-makers the weight of the dimension while modifying decision making process that applied fuzzy set theory to analyse the collected data.